Analisis Pengaruh Dimensi Kualitas Layanan Terhadap Loyalitas Pelanggan Bioskop XXI: Studi Kasus pada Pelanggan Bioskop XXI Mall Queen City di Kota Semarang - Andika Adi Darma; Suhaji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of service quality dimensions consisting of Tangibles, Reliability, Responsiveness, Assurance, and Empathy on customer loyalty of XXI Cinema at Queen City Mall, Semarang City. The benefits of this study are to provide a contribution to cinema management in understanding service factors that affect customer loyalty. By knowing the most influential dimensions, management can design more effective service improvement strategies, as well as build long-term relationships with customers through a more satisfying viewing experience. The method used in this study is a quantitative approach with a survey design. Data were collected through questionnaires distributed to 100 respondents who were customers of Cinema XXI. The data analysis technique used multiple linear regression assistance with SPSS 26 software, preceded by instrument validity and reliability tests, as well as classical assumption tests such as normality, multicollinearity, and heteroscedasticity to ensure the validity of the analysis model used. Based on the results of the analysis and discussion in this study, it can be concluded based on the results of the t-test that Tangibles (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), and Empathy (X5) have a positive influence on Customer Loyalty (Y) with the highest influence being the variables X1 and X4 Tangibles and Assurance, so to increase Customer Loyalty, it is necessary to pay attention to the dimensions of service quality in order to attract more. Furthermore, based on the results of the f test, it shows that the significant value is 0.000 <0.05. So it can be concluded that Tangibles, Reliability, Responsiveness, Assurance, and Empathy together or simultaneously have a significant influence on Customer Loyalty at the XXI Queen City Mall Semarang cinema.